Cost-Effectiveness Analysis Of Ceftriaxone-Gentamicin And Ampicillin-Gentamicin In Pediatric Pneumonia At Hospital X Madiun - Wika, Wika Admaja; Shania Crhisnatasha Putri; Anggi Restyana; Yogi Bhakti Marhenta (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Pneumonia is an infectious disease caused by bacteria characterized by fever, chills, coughing up phlegm, and breathing difficulty. Generally pneumonia is caused by an infection of Streptococcus pneumoniae bacteria. Antibiotics is a therapy used in pediatric pneumonia patients at hospitals X. in Madiun. This study aims to determine a more cost-effective antibiotics therapy combination between ceftriaxone-Gentamicin and Ampicillin-Gentamicin in pediatric pneumonia patients at Hospital X in Madiun in 2019-2021. This study used a cross sectional design and data collection was carried out retrospectively. There were 39 patients as samples who were pediatric patients aged ≤ 12 years who were adjusted to the inclusion criteria. The datawere identified using decision trees and analyzed cost-effectiveness with ACER and ICER calculations. The ACER value of Ceftriaxone-Gentamicin antibiotic therapy is IDR 6,047,334.23, which is lower than Ampicillin-Gentamicin therapy whch is of IDR 9,730,746.21, thus showing that Seftriaxone-Gentamicin is more cost-effective than Ampicillin-Gentamicin. The ICER calculation has negative result of Idr 500,953.74 so it shows that the Ceftriaxone-Gentamicin combination antibiotic is more cost-effective.